Composition and U—Pb ages of apatite in the Amba Dongar carbonatite–alkaline complex, India. (15th October 2018) - Fosu, Benjamin R.; Ghosh, Prosenjit; Chew, David M.; Viladkar, Shrinivas G.
Abstract: The Amba Dongar carbonatite‐alkaline complex is regarded as a late phase intrusion ( ca . 65 Ma) associated with Deccan volcanism. Existing age constraints on the Amba Dongar carbonatite are based on phlogopite 40 Ar– 39 Ar plateau ages derived from carbonatite and associated alkaline rocks within the complex. We explore the utility of apatite, a common accessory mineral in Amba Dongar carbonatites, as a petrogenetic and geochronological tool to constrain further the evolution of the carbonatites. Apatite exhibits different crystal forms—from hexagonal stubby prisms to ovoid and elongate grains. Apatite occurs as cumulate and disseminated grains that are either primary, fractured, or recrystallized. SrO content is high in primary apatite (3.17 wt%) but less in recrystallized (1.90 wt%) and disseminated grains (0.47 wt%). MnO and Cl are negligible while FeO is typically low in all samples. SiO2 content is low except for a few primary grains which measure up to 1.35 wt%, correlating with high REE content. LREEs dominate the total REE budget of Amba Dongar apatite, with HREEs below EPMA detection limit in most samples. Total REE content is generally low, though some primary apatite contains up to 3.19 wt% REEs. We also report UPb apatite ages from the carbonatites analysed in situ by LA‐ICP‐MS. The data from all samples combined on a UPb Tera–Wasserburg concordia yield a lower intercept age of 65.4 ± 2.5 Ma (MSWD = 2.8, 207 Pb/ 206 Pb i  = 0.8272 ± 0.0028), and the Amba Dongar carbonatites are thus interpreted to represent a phase of coeval magmatic activity with Deccan volcanism.